The Diversity of Food Plant Species in Cirahab, Curuggoong Village, Padarincang District, Serving as a Food Source for the Local Community - Hermawan Hermawan; Fitri Fitri; Wulan Wulan (Transpublika Publisher, 2026)
Plants play a vital role for humans, particularly food crops. These plants are widely utilized by the community for daily needs, including as sources of food and health-promoting beverages. This study aimed to determine the species diversity level of food crops in the Cirahab Bathing Area. Sampling was conducted by mapping the area using a 20 x 20-meter transect method. Environmental conditions including temperature, humidity, light intensity, wind speed, soil pH, and soil moisture were also measured. The plants identified included 5 jackfruit trees, 20 banana trees, 2 breadfruit (sukun) trees, 2 stink bean (jengkol) trees, 2 bitter bean (petai) trees, 5 red chili plants, 3 ginger plants, 1 bamboo clump, 10 taro plants, 5 fern plants, and 7 coffee plants. These plants were found within the Cirahab Bathing Area. Measurement results indicated environmental conditions of 32°C temperature, 90% air humidity, 89% light intensity, 0.75-5.8 m/s wind speed, a soil pH of 7, and soil moisture levels of 4-8. The plant diversity index value was 2.441, which, based on the diversity index formula, indicates a “moderate” level of diversity.